Applying Concepts of Inclusive Design in Sensory Product Design for Children - Moreira, Leonardo [UNESP]; Almendra, Rita Assoreira; Ferreira Barata, Tomas Queiroz; Raposo, D.; Neves, J.; Silva, J.; Castilho, L. C.; Dias, R. (Springer, 2021)
This paper aims to present the results of an investigation succeeding a Internship of Research Abroad (BEPE/FAPESP) which sought to expand the theoretical framework on design processes of sensory products in the European Market. The emphasis is on toys for children with blindness or low vision, from its design process all though its physical prototyping. This study structure follows: (a) theoretical deepening on children with visual impairment and the design practice of sensory products; (b) synchronic analysis of similar products available in the Portuguese Market; (c) design conception in the levels of project, generation and selection of alternatives; (d) Experimental execution of virtual and physical models in laboratory; (e) documentation and analysis of the results. Thus, this research intends to contribute to the development of sensory products for children with visual impairment, and encourage further research in the areas of Product Design and Inclusive Design.
Keywords: Inclusive design; Product design; Children with visual impairment; Sensory products